2018
DOI: 10.2217/rme-2017-0061
|View full text |Cite
|
Sign up to set email alerts
|

Heart Valve Tissue Engineering: An Overview of Heart Valve Decellularization Processes

Abstract: Despite recent advances in medicine and surgery, many people still suffer from cardiovascular diseases, which affect their life span and morbidity. Regenerative medicine and tissue engineering are novel approaches based on restoring or replacing injured tissues and organs with scaffolds, cells and growth factors. Scaffolds are acquired from two major sources, synthetic materials and naturally derived scaffolds. Biological scaffolds derived from native tissues and cell-derived matrix offer many advantages. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…The time-course experiments revealed that the Runx2 level peaked at 14 days of activation with either HGOM or OM. These data confirm the studies showing the highest expression of Runx2 at 14 days of VIC incubation in medium containing osteogenic factors [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…The time-course experiments revealed that the Runx2 level peaked at 14 days of activation with either HGOM or OM. These data confirm the studies showing the highest expression of Runx2 at 14 days of VIC incubation in medium containing osteogenic factors [49,50].…”
Section: Discussionsupporting
confidence: 91%
“…This renders them unideal, particularly in pediatric patients who will have to undergo multiple surgeries and intervention redoes throughout their life, with an augmenting risk of morbidity and mortality, and exacerbated quality of life. This has been the driving force of a relatively novel field of research known as heart valve tissue engineering in which early approaches have concentrated on developing new viable tissue via scaffold engineering, cells, and growth factors with the capability to grow in the body via use of a matrix that is seeded in vitro with harvested cells (13, 79). Tissue engineered heart valves (TEHVs) are flexible (can adapt and grow with age), non-thrombogenic, non-immunogenic, durable in all age groups (not just in older groups unlike BHVs, which will eliminate reoperations), and have ameliorated cellular viability making them advantageous over MHV and BHVs.…”
Section: Resultsmentioning
confidence: 99%
“…Among different types of TEHV, the decellularized ones (dTEHV) have attracted the interest, because of their low cost, simple preparation protocols and their similarity to the native valves. Till 2020 more than 80 articles and reviews have introduced and evaluated the use of these dTEHV [36][37][38][39][40][41][42][43][44]. Despite the relatively poor knowledge of calcification possible mechanisms in those types of heart valves, several research groups pointed to the role of immunogenicity and cell remnants as the main culprits in the calcification [10].…”
Section: Calcification Of Decellularized Heart Valvesmentioning
confidence: 99%